Islamic Counseling Guidance in Increasing the Maturity of Student’s Career - Sugandi Miharja (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2019)
This research aims to develop the format of Islamic career guidance through lectures in an effort to improve optimal career maturity with good processes and results. The research method combines quantitative and qualitative methods together. This research involved a department of Islamic Guidance and Counseling, Faculty of Da'wah and Communication, State Islamic University Bandung. The results showed that, there were four methods as efforts to intervene career advancement, they are career theory lectures, career portfolios, field trips, student presentations of career inspiration read from books. Different time share method for portions. Better than more interesting. The final result of career maturity through career guidance courses can achieve high career maturity. This research can be widely used as an effort to improve career progress through career guidance.Penelitian ini bertujuan membangun format bimbingan karir Islam melalui perkuliahan dalam upaya meningkatkan kematangan karier yang optimum secara proses maupun hasil yang baik. Penelitian menggunakan metode kombinasi antara pendekatan kuantitatif dan kualitatif secara bersama-sama. Penelitian ini melibatkan satu jurusan Bimbingan Konseling Islam, Fakultas Dakwah dan Komunikasi, UIN Bandung. Hasil penelitian menunjukkan bahwa terdapat empat metode sebagai upaya intervensi kematangan karier, yakni; ceramah teori karier, portofolio karier, kunjungan lapangan, presentasi mahasiwa dan buku bacaan inspirasi karier. Hasil akhir tindakan kematangan karier melalui mata kuliah bimbingan karier dapat mencapai kematangan karier tinggi dan sangat tinggi. Penelitian ini dapat digunakan secara luas sebagai upaya peningkatan kematangan karier melalui bimbingan karier.